Creative Responses to a Drug- or Alcohol-Related Death: A Sociocultural Analysis. (October 2015) - Valentine, Christine; Walter, Tony
This article takes a sociocultural approach to examining creative responses to a traumatic death and loss and their contribution to further understanding of grief, identity, and continuing bonds. Based on qualitative interviews with family members bereaved after a drug- or alcohol-related death, the article explores how, in circumstances which threaten identity and continuity of being, grief may find expression through public and private creativity. Indeed, such creativity was apparent despite negative cultural representations of such deaths invalidating the grief of those left behind, who may suffer profound guilt, isolation, and disturbing memories. While interviewees reported such negative effects, psychologically considered symptomatic of complicated grief disorder, they also conveyed creative responses to negative stereotypes, rebuilding identities, and continuing bonds. These responses, through which interviewees communicated both vulnerability and resilience, revealed a complex and nuanced picture of grief following traumatic loss.